PSYCHOLOGICAL FACTORS OF THE MODERN NUCLEAR FAMILY DEVELOPMENT - Hanna Anatoliivna Krupnyk (Insight: the psychological dimensions of society, 2019)
An overview of the state of the modern nuclear family has been provided in the article. The scientific works of leading domestic and foreign modern scientists have been analyzed. The features of interaction of family members and the factors that affect it have been highlighted. The modern family has acquired new peculiar features that distinguish it from the traditional entrenched imagination and bring it to a new level, which allows us to definde the change of the centuries-old tradition of the family image. Most psychologists in their research works point to such trends in the development of the family in modern society as the prevalence of career, noting that this is the cause of the growth of the welfare of the family; rather later, compared with previous years, marriage and postponement of the birth of descendants; nuclearization of the family as its simplification. Modern science shows an increasing of divorce and remarriage; indicates that there is a variability of forms of interpersonal relationships, which later develop into family relationships.Purpose of research: to highlight the features of psychological factors of the development of modern nuclear family. Methods: analysis, synthesis of the provisions contained in the psychological literature on the development of modern nuclear family, comparison, generalization, interpretation and systematization of theoretical and empirical research. A successful family is a family with a high level of family morality, spirituality, mutual support and mutual assistance, with rational methods of solving family problems. Results, conclusions: Leading experts note that family well-being is ensured by humanity in relations, the ability to love and respect each other. In such a family, when solving intrafamily problems, there is a high coherence of actions, mutual respect and mutual understanding generating a positive moral atmosphere. Among the attributes of a strong family, scientists distinguish such factors as: mutual love; mutual respect; mutual understanding; willingness to help; responsibility; high level of trust in the couple; friendly communication. On the other hand, the evidence of disharmony of the family is the weakening or breaking of the connection in the system of "spouses-parents-children", which arise as a result of excessive employment of the father or mother, conflict situation in the family, antisocial behavior of family members, cases of violence or abuse, lack of a happy emotional atmosphere in the family, disharmonious relations in the family.